Equal Access to the Vaccination of Covid-19 in Southeast Asia: Can ASEAN be a Catalyst? - Muhammad Insan Tarigan; Raisha Hafandi (Hasanuddin Law Review, 2021)
Since the time Covid-19 was discovered in Southeast Asia, around 2.5 million people have been infected and more than 54 thousand have died by early March 2021. Even though ASEAN members have followed most of the WHO recommendations to deal with Covid-19, cases are still liable to increase. Therefore, vaccine utilization is the best chance which people believe in to fight the pandemic for now. However, the vaccine’s availability and distribution are a dilemma for the ASEAN member countries. Therefore, this article aims to determine the possibility of ASEAN’s role in creating equal access to the Covid-19 vaccine for everyone. According to the juridical normative research, ASEAN is committed to protect and promote human rights and to realize the Sustainable Development Goals (SDGs). On that basis, the organization tends to play an important role in Covid-19 vaccination in Southeast Asia by cooperating with its partners to research and create the required vaccine.